Simulation and Optimization of a Self-Cleaning Device for the Header of a Rice Seed Harvester Using Fluent–EDEM Coupling - Yiren Qing; Lu Chen; Dongquan Chen; Peiyu Wang; Wenbin Sun; Ranbing Yang (Agriculture)
Rice seed production is a critical step in breeding high-quality varieties. To ensure seed purity, it is essential that no residual grains or broken ears remain in the harvester header after harvesting each variety, thus preventing cross-contamination. This study addresses the issue of seed retention in existing rice harvesters, which lack efficient self-cleaning or other cleaning mechanisms and cannot be cleaned rapidly. A self-cleaning device for the harvester header was designed to enable one-click cleaning after harvesting a single variety. A novel cleaning nozzle was developed as the key component of the device, with its structure optimized through single-factor and orthogonal combination experiments. The number of nozzles was determined based on their spray width and the header width. A header-cleaning airflow simulation model based on Fluent–EDEM coupling was constructed to investigate the effects of nozzle inlet pressure, airflow incident angle, and nozzle outlet height on the self-cleaning rate. Optimal cleaning parameters were identified to maximize the self-cleaning rate, and the simulation results were validated. The study revealed that the nozzle’s expansion section length, throat diameter, and contraction section length significantly affect the spray width. When the expansion section length was 10 mm, the throat diameter was 8 mm, and the contraction section length was 8 mm, the nozzle achieved the largest jet angle, measuring 50.3 cm. Further analysis indicated that inlet air pressure had the greatest influence on the self-cleaning rate, followed by airflow incident angle and nozzle outlet height. The optimal parameter combination was identified as an inlet air pressure of 0.6 Mpa, an airflow incident angle of 118.25°, and a nozzle outlet height of 2.64 mm, achieving a maximum self-cleaning rate of 99.63%. A one-click cleaning system was designed using an STM32 microcontroller and hardware circuits. Field experiments under optimal parameters demonstrated a self-cleaning rate of 97.68% with a cleaning duration of 10 s per cycle. The findings provide theoretical guidance for the design and optimization of self-cleaning headers for rice seed production.